Benefits of switching from activity- based costing to resource consumption accounting: evidence from a power generator manufacturing plant / Suaad Jassem - Jassem, Suaad (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam:, 2019)
In a globalized and highly competitive business environment, dynamic and precise cost accounting information has become vital for supporting effective planning and decision-making. Traditional accounting systems that provide variable- and fixed-cost information without an adequate view of how resources are being utilized do not provide sufficient information to decision-makers to allow them to streamline the organization’s value chain. With the advent of relatively newer accounting systems such as Resource Consumption Accounting, it is now possible for managers to track resource cost flows with pinpoint accuracy. The Resource Consumption Accounting approach is a combination of the German Marginal Cost Accounting and Activity-Based Costing systems that enables the generation of marginal cost statements, which provide precise resource utilization information, and identifies excess or idle capacities of such resources. The current research used a case study of a manufacturing organization based in Southeast Asia with regional presence that used the Activity-Based Costing system for several years and then switched to the Resource Consumption Accounting system. The study demonstrates how the marginal cost statements between Activity-Based Costing and Resource Consumption Accounting differ in the manner in which they present information and how the organization has benefited by identifying the excess resource capacity and tracking resource consumption through Resource Consumption Accounting system.